2009
DOI: 10.1177/009286150904300304
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Customer Satisfaction with Verbal Responses Provided by a Pharmaceutical Company’s Third-Party Medical Information Call Center

Abstract: Our purpose was to conduct a customer satisfaction survey of verbal responses provided by a pharmaceutical company's third-party medical information (MI) call center. One survey for health care providers (HCPs) and one for consumers were designed to assess customer satisfaction following a verbal response to an MI question. Surveys were offered to all HCPs and consumers contacting the MI call center January-March 2007. Respectively, 27% and 18% of all HCPs and consumers (N = 318) receiving a verbal response ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…Additional efforts toward increasing this rate of return included revision of evaluation cover letter to specify return methods available and addition of follow-up contacts to participants of evaluations not received within 2 weeks from the date distributed. We offered multiple methods of return for evaluations, including phone, mail, email, and fax because data indicates this increases the rate of return (Black et al 2009;McCluskey and Topping 2011).…”
Section: Methodsmentioning
confidence: 99%
“…Additional efforts toward increasing this rate of return included revision of evaluation cover letter to specify return methods available and addition of follow-up contacts to participants of evaluations not received within 2 weeks from the date distributed. We offered multiple methods of return for evaluations, including phone, mail, email, and fax because data indicates this increases the rate of return (Black et al 2009;McCluskey and Topping 2011).…”
Section: Methodsmentioning
confidence: 99%
“…In addition to interactive voice response surveys, companies are using interviews, mystery shoppers, and electronic and hard-copy surveys. 14 Companies that conduct these surveys gain a better understanding of their customers' views of their service, and they have a measurable baseline of customer satisfaction to evaluate the impact of changes in their systems, personnel, or information provided. The data provided by these surveys can be used to drive changes to the medical information department and throughout the organization.…”
Section: Customer Surveysmentioning
confidence: 99%
“…In addition to interactive voice response surveys, companies are using interviews, mystery shoppers, and electronic and hard-copy surveys. 14…”
Section: Customer Surveysmentioning
confidence: 99%
“…2 In fact, several studies have demonstrated that, in general, HCPs are satisfied with the information they received from industry-based MI departments (Pfizer Inc, unpublished data). 3 -6 Given the extensive and high-quality information that MI departments from pharmaceutical companies have, why is this resource not used more frequently among HCPs? What are the factors that determine utilization of a medical information resource?…”
Section: Introductionmentioning
confidence: 99%